DINAMIKA TOLERANSI DI KOTA BESAR INDONESIA: PERAN PEMERINTAH KOTA YOGYAKARTA DALAM MEWUJUDKAN CITY OF TOLERANCE - Siti Maharani Chumairah; Ridho Al-Hamdi (Lembaga Riset dan Pengkajian Strategi Pemerintahan IPDN, 2019)
This paper examines the role of Yogyakarta City Government in realizing the city of tolerance. The tolerance in this context is including race, culture, and religion. Methodologically, this paper is research-based paper by employing qualitative method and the case study as the research approach. Yogyakarta City was selected as the case because of the motto of “city of tolerance”. In data gathering, this paper applies in-depth interview and documentation. To measure the role of the government, this paper uses three indicators: the role as the regulator in issuing regulations and policies, the role as the dynamist in terms of guidance and training, and the role as the facilitator in providing facilities to the community. The finding demonstrates that the government of City of Yogyakarta has succeeded to realize its motto of “city of tolerance” through those three roles. Among the three indicators, the role as the dynamist is more powerful than other indicators in realizing the city of tolerance.